2020
DOI: 10.1002/ejoc.202000136
|View full text |Cite
|
Sign up to set email alerts
|

The Retro‐Claisen Rearrangement of 2‐Vinylcyclopropylcarbonyl Substrates and the Question of its Synthetic Potential

Abstract: The retro-Claisen [3,3]-sigmatropic rearrangement of ,enoyl compounds allows to form a CO bond while breaking a CC bond in a concerted process. It is rarely observed with acyclic substrates. However, when the alkene and carbonyl groups are tethered by a cyclopropane, this rearrangement results in ring expansion, to form a 2,5-dihydrooxepine whose stability entirely depends on the substitution pattern. After its discovery in the 1960's, applications have resulted in the development of original methodologies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Loss of acetic acid from the precursor ion yields a methaniminium ion 7 with m / z 128.2, which may further lose formic acid to give 8 with m / z 82.1. Retro Claisen rearrangement (RCR) 22 of 5 yields 9 followed by loss of a ketene molecule to generate 2‐hydroxy‐1‐methylenepyrrolidinium ion ( 10 ) with m / z 100.1, which may lose a methanimine molecule to give m / z 71.1 ( 11 ). The m / z 73.0 fragment may be the protonated β‐propiolactone ( 12 ) directly formed from the precursor ion by loss of the proline moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of acetic acid from the precursor ion yields a methaniminium ion 7 with m / z 128.2, which may further lose formic acid to give 8 with m / z 82.1. Retro Claisen rearrangement (RCR) 22 of 5 yields 9 followed by loss of a ketene molecule to generate 2‐hydroxy‐1‐methylenepyrrolidinium ion ( 10 ) with m / z 100.1, which may lose a methanimine molecule to give m / z 71.1 ( 11 ). The m / z 73.0 fragment may be the protonated β‐propiolactone ( 12 ) directly formed from the precursor ion by loss of the proline moiety.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent report we demonstrated that this spontaneous rearrangement could be applied to the total synthesis of radulanin A, a 2,5-dihydrobenzoxepin. [24] Before our work, probably due to the reputed kinetic instability of 2,5-dihydrooxepins ( 5), [24][25][26] the retro-Claisen rearrangement had never been considered as a key step in the total synthesis of oxepane-based natural products, [27] although the reaction was fortuitously observed during Reisman's synthesis of salvileucalin B [28] or used by Boeckman to achieve the synthesis of the eight-membered natural product (+)-laurenyne. [29] Furthermore, the oxidation of a 2,5-dihydrooxepin (8), prepared by ring-closing olefin metathesis of a diene (7), to an oxepin has only been investigated by Taylor and co-workers during the synthesis of (�)-2 (Figure 1C).…”
Section: Introductionmentioning
confidence: 99%
“…18 Incidentally, we recently reported the total synthesis of some of those oxepin natural products. 19,20 In 1994, Danishefsky reported the first total synthesis on Nacetylardeemin, 21−23 a compound that reverses the multidrug resistance of cancer cells. 24 It featured a pivotal aza-Wittig reaction for the closure of the central ring, forging the C�N bond of the piperazino[2,1-b]quinazolin-3,6-dione core (Scheme 1a).…”
mentioning
confidence: 99%